2015
DOI: 10.1177/1077801215593647
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between ADHD and the Risk of Sexual Victimization Among College Women

Abstract: Using data from a nationally representative sample of college women, the current study examines attention deficit hyperactivity disorder (ADHD) as a potential risk factor in the prediction of sexual victimization among college women and as an extension of the lifestyles/routine activities framework. The findings indicate that college women with ADHD experienced sexual victimization at significantly higher rates than college women without ADHD. Furthermore, ADHD emerged as a significant predictor of sexual vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 45 publications
8
80
1
Order By: Relevance
“…Future studies that include students with other disabilities will add to our understanding of how disability intersects with alcohol use and violence victimization. Second, we did not use diagnostic tools to assess disability; rather, we used selfreported disability, an approach that has been used in many prior studies (American College Health Association, 2016;Hossain et al, 2014;Scherer et al, 2013Scherer et al, , 2016aSnyder, 2015). To provide expanded clarity in the relationships between disability, alcohol, and IPV/SV, future studies might consider using a diagnostic interview to assess disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies that include students with other disabilities will add to our understanding of how disability intersects with alcohol use and violence victimization. Second, we did not use diagnostic tools to assess disability; rather, we used selfreported disability, an approach that has been used in many prior studies (American College Health Association, 2016;Hossain et al, 2014;Scherer et al, 2013Scherer et al, , 2016aSnyder, 2015). To provide expanded clarity in the relationships between disability, alcohol, and IPV/SV, future studies might consider using a diagnostic interview to assess disability.…”
Section: Discussionmentioning
confidence: 99%
“…College women with a mental health disability (e.g., depression, attention deficit hyperactivity disorder [ADHD]) are at elevated risk of sexual violence (SV) and intimate partner violence (IPV), with serious health consequences (Bonomi, Nichols, Kammes, & Green, 2018; Hossain, Memiah, & Adeyinka, 2014; Scherer, Snyder, & Fisher, 2013, 2016a; Snyder, 2015). Hossain et al used the National College Health Assessment (NCHA) data to show that having a depression diagnosis increased college women’s risk of SV (odds ratio [OR] = 1.56), even after controlling for other risk behaviors (Hossain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different psychiatric disorders and physical disabilities among children and adolescents have been associated with an increased risk of sexual victimization (Jones et al, 2012). Autism spectrum disorder (ASD), Attentiondeficit/Hyperactivity disorder (ADHD), and other related neurodevelopmental disorders (NDDs) might potentially elevate the risk of being sexually abused (Sevlever, Roth, & Gillis, 2013;Snyder, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that ADHD symptoms lead to an increased risk for potentially dangerous situations is supported by a study on over 14,000 female students. Here, those with ADHD had a significantly higher rate of unwanted sexual contacts and rape, and the risk for PTEs was increased by concomitant alcohol and drug use [33]. Also, other studies that did not specifically address ADHD identified alcohol use as a risk factor for sexual victimization [34][35][36].…”
Section: Discussionmentioning
confidence: 86%